European Policy Convergence and the EMS. (IMF Working Papers; Working Paper ;, 1990)
In this paper we analyze the degree of policy convergence of EMS member countries relative to that of some non-EMS countries. Interestingly, we find convergence for the nominal and real exchange rates and money supplies of the EMS members but not for the non-EMS countries. We also provide some evidence to support the 'German leadership hypothesis' in the context of intra-EMS monetary policy convergence.